2022
DOI: 10.1155/2022/2181525
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Novel Immune Subtypes Characterized by Distinct Prognosis and Tumor Microenvironment in Osteosarcoma

Abstract: Osteosarcoma is a kind of primary malignant tumor of bone. In recent years, its therapeutic effect and prognostic survival are dissatisfactory. The tumor immune microenvironment (TIME) reflects immune status of patients, but it is little known in osteosarcoma. Therefore, this study attempts to conduct a comprehensive analysis to explore TIME of osteosarcoma and identify TIME-related subtypes for clinical management and treatment. We successfully established two novel tumor immune infiltration clusters (TIIC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…We found significantly higher levels of immune cells in the low-risk group than that in the high-risk group, with the exception of M0 macrophages. Previous evidence suggests that prolonged immune responses and the composition of the tumor microenvironment are significant factors that determine OS prognosis [ 41 , 42 ]. Tan et al previously reported that the tumor microenvironment was helpful in identifying the signature of immunotherapy-relevant and prognostic genes [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found significantly higher levels of immune cells in the low-risk group than that in the high-risk group, with the exception of M0 macrophages. Previous evidence suggests that prolonged immune responses and the composition of the tumor microenvironment are significant factors that determine OS prognosis [ 41 , 42 ]. Tan et al previously reported that the tumor microenvironment was helpful in identifying the signature of immunotherapy-relevant and prognostic genes [ 43 ].…”
Section: Discussionmentioning
confidence: 99%